TINGKAT KONSERVATISME AKUNTANSI DI INDONESIA DAN HUBUNGANNYA DENGAN KARAKTERISTIK DEWAN KOMISARIS SEBAGAI SALAH SATU MEKANISME CORPORATE GOVERNANCE (Studi Empiris Pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Achmad Fatih Syahrul Mubarok (Universitas Islam Malang, 2017)
ABSTRACTThis research is conducted with the purpose of: 1) To determine theinfluence of the independence of the commissioner, share ownership bycommissioners and board of commissioner size, audit committee on the level ofaccounting conservatism simultaneously. 2) To determine the influence of theindependence of the commissioner, share ownership by commissioners and boardof commissioner size, audit committee on the level of accounting conservatismpartially.The population used in this study are all LQ45 companies listed on theIndonesia Stock Exchange (BEI) in 2013-2015. Sample selection using purposivesampling. Based on the criteria, obtained 25 companies that become samples inthis study. The method used in this study using multiple linear regression method.Based on the results of the analysis can be put forward severalconclusions as follows: 1) F test results measured by the size of accruals andmeasured by market value indicates that the independent variables simultaneouslyor together significantly (tangible) to the dependent variable. 2) The result of ttest is measured by accrual size indicates that for independent variableIndependence of the board of commissioners partially significant influence tovariable Conservatism with accrual sizes, whereas for variable managerialownership, The size of the board of commissioners, audit committee, Institutionalownership, laverage and Company size partially no effect to variableConservatism with accrual sizes. 3) The result of t test with market size indicatesthat the independent variables Conservatism with accrual sizes, The size of theboard of commissioners, and laverage are partially significant to Conservatismwith market size, while managerial ownership, audit committee, Institutionalownership, and Company size variables do not have an effect on Conservatismwith market size.Keyword : independence of the commissioner, share ownership by commissionersand board of commissioner size, audit committee, accounting conservatism